Penerapan Strategi Card Sort Untuk Meningkatkan Keaktifan Dan Hasil Belajar Ipa Siswa Kelas Iii Sd Negeri Singkil Boyolali Tahun Ajaran 2015/2016 - PANGESTIKA, WIDIYA (2016)
Widiya Pangestika / A510120007; IMPLEMENTATION CARD SORT STRATEGY TO IMPROVE ACTIVITY AND LEARNING OUTCOMES SCIENCE CLASS III ELEMENTARY OF PUBLIC SCHOOL SINGKIL BOYOLALI IN ACADEMIC YEAR 2015/2016. Essay, The Faculty of Education, University of Muhammadiyah Surakarta. Februari 2016. Problems in the background of this study was the low activeness of students in learning science, causing student learning outcomes to be low. This research aims to improve learning outcomes Science Activity and third grade students of Elementary of Public School Singkil Boyolali in Academic year 2015/206 through learning strategies card sort. Data collection techniques used were interviews, observation, consuming method tests, and documentation. Test the validity of using the technique of triangulation of sources and triangulation methods. Data analysis: data reduction, data display, and conclusion. The results showed an increase in activity of students in learning science. This can be proved in the results of the activity indicators of student learning achievement and learning outcomes as follows: 1 activeness of students in teachers' attention to the explanation of 34, 8% (pre-cycle) to 91.3% (the second cycle II meeting). Active students in asking questions of 21.7% (pre-cycle) to 82.6% (the second cycle II meeting). Active students in answering questions from 17.4% (pre-cycle) to 91.3% (the second cycle II meeting). Student activity in conducting the game according to the rules from 52.2% (pre-cycle) to 86.9% (the second cycle II meeting). Involvement of the student in completing a task from 60.9% (pre-cycle) to 91.3% (the second cycle II meeting). So students with high learning activeness of 21.7% (pre-cycle) to 91.3% (cycle II meeting II) and students who completed the study of 39.1% (pre-cycle)to 95.6% (the second cycle II meeting). The study concluded that the implementation of the strategy card sort in science learning can enhance the activity of third grade students of SD Negeri Singkil Boyolali Academic Year 2015/2016.